Strain-release arylations for the bis-functionalization of azetidines. Issue 15 (2nd February 2022) - Trauner, Florian; Reiners, Felix; Apaloo-Messan, Kodjo-Edmond; Nißl, Benedikt; Shahbaz, Muhammad; Jiang, Dongfang; Aicher, Julian; Didier, Dorian
Abstract : Introducing azetidine-linkers between two aryl moieties is made possible through strain-release strategies. Abstract : The addition of nucleophilic organometallic species onto in situ generated azabicyclobutanes enables the selective formation of 3-arylated azetidine intermediates through strain-release. Single pot strategies were further developed for the N -arylation of resulting azetidines, employing either SN Ar reactions or Buchwald–Hartwig couplings.